Nickel‐Catalyzed Arylboration of Alkenylarenes: Synthesis of Boron‐Substituted Quaternary Carbons and Regiodivergent Reactions. (28th June 2019) - Chen, Liang‐An; Lear, Alan R.; Gao, Pin; Brown, M. Kevin
Abstract: A method for the construction of boron‐substituted quaternary carbons or diarylquaternary carbons by arylboration of highly substituted alkenylarenes is presented. A wide range of alkenes and arylbromides can participate in this reaction thus allowing for a diverse assortment of products to be prepared. In addition, a solvent dependent regiodivergent arylboration of 1, 2‐disubstituted alkenylarenes is presented, thus greatly increasing the scope of products that can be accessed. Abstract : Borsubstituierte quartäre Kohlenstoffatome oder diarylquartäre Kohlenstoffatome werden durch Arylborierung von hochsubstituierten Alkenylarenen erzeugt. Ein breites Spektrum von Alkenen und Arylbromiden kann an dieser Reaktion teilnehmen. Außerdem wird eine lösungsmittelabhängige regiodivergente Arylborierung von 1, 2‐disubstituierten Alkenylarenen vorgestellt, welche das Produktspektrum noch mehr erweitert.